The Concept of Special Judicial Institutions in Dispute Resolution of Village Heads In Indonesia - Fauziyah Fauziyah; I Wayan Parsa (University of Udayana, 2020)
The idea of village head dispute resolution through the Special Judicial Institution began with anxiety over Law 6 of 2014 concerning Villages, Government Regulation number 6 of 2014 concerning Implementation of Village Laws, and Minister of Home Affairs Regulation No. 112 of 2014 concerning Guidelines for Election of Village Heads, which has not yet regulated the village head election supervisory institutions and dispute resolution institutions for village head elections. The institutions that are required to complete based on these rules are Regents with a period of 30 days. Regents are political positions which also have many political interests. The existence of this decision had an impact on one of the candidates for the village head. The current practices for resolving disputes over village head elections through the District Court and the State Administrative Court. The purpose of this study to create a concept for regional special judiciary institutions in resolving regional election disputes in Indonesia. This research using a normative juridical approach with a statute approach, history approach and conceptual approach. The results of the study show that by establishing a special independent judicial institution based on local wisdom by prioritizing the principle of kinship and consensus building. The main task of the institution is to assist the regional head in providing alternative legal services, to serve and protect the rights of the parties in seeking truth and justice, and to settle according to a predetermined time, to try to examine and decide on cases of village head election disputes.